'Greeting! it's the people's greeting to Ousmane Haïdara', or the popular reason for Islamic praise - (:unkn) unknown (My University, 2017)
The aim of this text is to give an account of the very contemporary production methods of a Malian preacher, Chérif Ousmane Madani Haïdara, through the study of an Islamic praise song zikiri (from the Arabic dhikr, lit. “repeated invocation of the name of Allah”) composed for him. In his twenty-five-year career, this preacher has become one of the leading figures in West African religious entrepreneurship, and has profoundly altered the public expression of Islam in Mali (Davis, 2002; Schulz, 2007; Holder, 2012). Not just because he is charismatic, uses audiovisual means and preaches in stadiums, all things evocative of evangelical preachers, but because he is based on an organization without equivalent in the sub-region: Ançar Dine , created in 1991 in the wake of Mali's democratic process, before becoming Ançar Dine International in 2004, then the Ançar Dine International Federation in 2012-2013. Although it is present in some thirty countries, mainly in Africa, but also in Europe, North America and as far afield as China, Ançar Dine is essentially active in Mali, Côte d'Ivoire and Burkina Faso, three countries situated in the Mandingo linguistic space and that of cross-border circulation.
Keywords: African Research